The Relationship Between Students' Digital Game Addiction and Their Attitudes and Habits Towards Reading - Kaman, Şafak; Bulut, Aydın (Kastamonu Egitim Dergisi, 2024)
Purpose: The aim is to determine the relationship between middle school students' levels of digital game addiction and their attitudes and habits towards reading. Design/Methodology/Approach: The study used a correlational survey model. This model introduces a survey approach aimed at determining the co-variation between two or more variables. The sample group of the study consisted of 324 secondary school students enrolled in the educational year 2023-2024 in the Kaman district of Kırşehir province. Data were collected using the "Digital Game Addiction Scale" and the "Attitude and Habit Scale Towards Reading." Findings: The collected data were analyzed using the SPSS 21 software package. Upon examining the findings of the study, it was determined that as students' digital game addiction increased, their attitudes and habits towards reading decreased. Conversely, as digital game addiction decreased, attitudes and habits towards reading increased. Additionally, it was observed that the levels of digital game addiction were higher in male students compared to female students. Highlights: The findings of this study, along with the literature review, indicate that whether they are children or adolescents, if digital games are not played in a controlled manner, it can lead to addiction. A child who has acquired digital game addiction may reduce the time allocated to their studies, start avoiding social environments, and may not be able to develop certain skills that would make them academically successful. It is crucial, especially for parents, to control the duration and type of digital games their children play.
Keywords: 4. Education